2022
DOI: 10.1136/bmjopen-2021-058416
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing COVID-19 vaccination uptake among community members in Hong Kong: a cross-sectional online survey

Abstract: ObjectiveVaccination is recognised as the most effective approach to contain the spread of the COVID-19 pandemic in the long run. However, the global vaccination uptake is still suboptimal. Although a considerable number of studies have focused on factors influencing intention or acceptance of COVID-19 vaccination, few explore the factors that affect actual vaccination uptake. This study aimed to explore the factors influencing COVID-19 vaccination uptake among the general public in a developed country.DesignA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
4
14
0
Order By: Relevance
“…This thought is strengthened by our findings that increased self-perceived severity of COVID-19 and the absence of COVID-19 diagnóstico in the past were associated with an increased likelihood of COVID-19 vaccination. Several studies confirm these results ( Lau et al, 2021 ; Pacella-LaBarbara et al, 2021; Wong et al, 2022 ). Risk perception regarding the COVID-19 is crucial in the decision of individuals to be vaccinated, since the intention to vaccinate is higher among those who consider the COVID-19 to be dangerous and life-threatening (Caserotti et al, 2021; Glöckner et al, 2020 ; Karlsson et al, 2021 ; Ward et al, 2020 ).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…This thought is strengthened by our findings that increased self-perceived severity of COVID-19 and the absence of COVID-19 diagnóstico in the past were associated with an increased likelihood of COVID-19 vaccination. Several studies confirm these results ( Lau et al, 2021 ; Pacella-LaBarbara et al, 2021; Wong et al, 2022 ). Risk perception regarding the COVID-19 is crucial in the decision of individuals to be vaccinated, since the intention to vaccinate is higher among those who consider the COVID-19 to be dangerous and life-threatening (Caserotti et al, 2021; Glöckner et al, 2020 ; Karlsson et al, 2021 ; Ward et al, 2020 ).…”
Section: Discussionmentioning
confidence: 64%
“…It is highly encouraging that the majority of participants had been vaccinated against the COVID-19 (87.8%). In similar studies, this rate was 28.6% in the USA and the United Kingdom ( Nguyen et al, 2021 ), 94.1% in the United Kingdom ( Glampson et al, 2021 ), 98% in the USA ( McCabe et al, 2021 ), 50.8% in Hong Kong ( Wong et al, 2022 ), and 22.4% in Saudi Arabia ( Al-Mansour et al, 2021 ). In addition, we found that the most important reasons why participants were not vaccinated were concerns about the safety, effectiveness and side effects of COVID-19 vaccines, previous COVID-19 diagnóstico, and females' effort to get pregnant.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Propaganda could highly affect the confidence in vaccinations due to the unknown of the newly emerged virus. There was an association between confidence in vaccines and health literacy [ 34 ]. The HK government constantly clarified the misinformation through daily press conferences and promoted proper health education through TV advertisements throughout the pandemic.…”
Section: Discussionmentioning
confidence: 99%